1980
DOI: 10.1111/j.1432-1033.1980.tb04423.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultraviolet Irradiation on 30‐S Ribosomal Subunits. Identification of the RNA Region Crosslinked to Protein S7

Abstract: The effects of ultraviolet irradiation on Escherichia coli 30-S ribosomal subunits were studied. At the doses of radiation used in this work (0-4.5 x lo5 quanta/30-S subunit), only protein S7 was found to be significantly crosslinked to the 16-S RNA. In conditions where 25 % of the protein was covalently crosslinked, the ability of the irradiated 30-S subunits to reassociate with 50-S subunits and their activity in polyphenylalanine synthesis decreased strongly. Similar results were obtained by irrradiation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1980
1980
1995
1995

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…studying photocross-linking of protein S7 and 16s RNA in 30s ribosomal subunits found that uracil and methionine were involved in adduct formation. [Other experiments (Ehresmann et al, 1980a) have indicated that cytosine is involved in cross-link formation in the S7-16s RNA system. ]…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…studying photocross-linking of protein S7 and 16s RNA in 30s ribosomal subunits found that uracil and methionine were involved in adduct formation. [Other experiments (Ehresmann et al, 1980a) have indicated that cytosine is involved in cross-link formation in the S7-16s RNA system. ]…”
Section: Introductionmentioning
confidence: 97%
“…The photochemical covalent cross-linking of proteins to RNA has been recently exploited as a tool to determine points of contact in RNA-protein complexes. Such systems as ribosomes (Zwieb and Brimacombe, 1979;Ehresmann et al, 1980a;Maly er al., 1980), aminoacyl-tRNA synthetase-tRNA complexes [for reviews, see Ebel et al (1979) and Schimmel (1979)l and RNA viruses (Ehresmann et al, 1980b) have been examined using the photocross-linking technique. To date, two points of contact have been characterized, both in ribosomal systems.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Ehresmann and his coworkers have presented evidence that S7 can be crosslinked to a site in the region 1261-1266 (A-C-C-U-C-G in Fig. 2A) (16). Therefore, we first compared the nucleotide sequence of this region (1220-1340; see refs.…”
Section: Gene Is Not Inhibited By L1 This and Other Experiments mentioning
confidence: 99%
“…However, other groups were able to crosslink many other proteins in other types of ribosomes (Paleologue et al, 1985) or with E. coli ribosome and tRNA ribosome complexes, yielding much information of structural interest (Turchinsky et al, 1978). Since the doses used (2-10 x lo5 quantdparticle) are in the same range, the different results reported could be accounted for in part by the different sensitivities of the detection methods: 1251 labeling (Turchinsky et al, 1978), silver staining (Paleologue et al, 1985) and Coomassie blue staining (Moller and Brimacombe, 1975;Ehresmann et al, 1980) and overall in vivo (32P)RNA labeling for detection of crosslinked oligonucleotides.…”
Section: Comparison Of the S4u Induced Crosslinks With Those Obtainedmentioning
confidence: 99%